Inclusion of P?Δ effect in displacement-based seismic design of steel moment resisting frames. - Asimakopoulos, Aristidis V.
A procedure for treating the P? Δ effect in the direct displacement-based seismic design of regular steel moment resisting frames with ideal elastoplastic material behaviour is proposed. A simple formula for the yield displacement amplification factor as a function of ductility and the stability coefficient is derived on the basis of the seismic response of an inelastic single degree-of-freedom system taking into account the P? Δ effect. Extensive parametric seismic inelastic analyses of plane moment resisting steel frames result in a simple formula for the dynamic stability coefficient as a function of the number of stories of a frame and the column to beam stiffness ratio. Thus, the P? Δ effect can be easily taken into account in a direct displacement-based seismic design through the stability coefficient and the yield displacement amplification factor. A simple design example serves to illustrate the application of the proposed method and demonstrate its merits.
Keywords: P?Δ effect; Seismic design; Displacement-based design; Plane steel frames; Moment resisting frames; Stability coefficient; Yield displacement; Amplification factor